REFORMASI BIROKRASI vs REMUNERASI - Sulistyo, Agustinus (Pusat Pelatihan dan Pengambangan dan Kajian Desentralisasi dan Otonomi Daerah Lembaga Administrasi Negara, 2012)
Bureaucracy reform became the government commitment with the aim of improving the performance of the government organization. Bureaucracy reform was carried out by improving the structure of the organization, improved business process, and improved the management of human resources. By running the bureaucracy reform, the government official will get remuneration that is taking the form of giving of the achievement allowance. But in fact, the condition that happened was the reverse. Organization carried out bureaucracy reform to receive remuneration. So bureaucracy reform that was carried out did not touch his root, but just met the condition for the documentation of bureaucracy reform and get the remuneration.